The RELATIONSHIP OF SERVICE QUALITY WITH GOJEK CUSTOMER SATISFACTION IN THE ENVIRONMENT OF INDONESIAN CHRISTIAN UNIVERSITY OF CAWANG - Lumantoruan, Rutman; Malau, Melinda (Fundamental Management Journal, 2018)
The advantage of ride hailing business in society is huge nowadays. Go-jek plays role in service company, provides opportunity for job applicants from various background to achieve good occupation. To improve customer satisfaction, Go-jek made standard for service quality. As many competitors in ride hailing business, it is important to provide better service quality for customer. From this study result, it could be concluded that Go-jek has performed in content and satisfied service level using Importance Performance Analysis (IPA) and Cartesius Analysis Quadrant model. IPA in all questions for level of customer satisfaction reached 80% which means â€œstrongly agreeâ€; besides for question: According to your experience with Go-jek, is Go-jekâ€™s fare proper to your travelled distance? Reached 79.29; question: Is Go-jek driver is keen to offer mask to you? Reached 71.12; question: Does Go-jek driver offer rain coat to you when rain downs? Reached 78.83 in â€œagreeâ€ scale. In the formation and examination of this study, using IPA model and Cartesius Analysis Quadrant, resulted that customer satisfaction in Go-jek service performance has been located in first and second quadrant, therefore second quadrant should be maintained and first quadrant should be improved to maximize Go-jekâ€™s customer satisfaction. Keyword: service quality, Go-jek